Navigating the Jungle of Possibilities: How to Protect Citizens from Soaring Energy Prices - Nadine Riedel; Andreas Peichl (Wirtschaftsdienst)
Abstract Living costs in Germany have surged since Russia’s attack on Ukraine. In this article, we discuss pros and cons of different government policies to protect affected citizens. There is a vast domain of possible relief options, each coming with its own trade-offs and design pitfalls. Information gaps in German public administration render desirable options like income and energy-use-contingent transfers administratively infeasible. These frictions should be addressed — if not for the present, then for the next crisis. With regard to other options, governments must be mindful to design policies that are well-targeted to people in need and that do not distort incentives to reduce energy consumption. Possibilities for that do exist.